2017
DOI: 10.1104/pp.17.00311
|View full text |Cite
|
Sign up to set email alerts
|

Ripening Transcriptomic Program in Red and White Grapevine Varieties Correlates with Berry Skin Anthocyanin Accumulation

Abstract: Grapevine () berry development involves a succession of physiological and biochemical changes reflecting the transcriptional modulation of thousands of genes. Although recent studies have investigated the dynamic transcriptome during berry development, most have focused on a single grapevine variety, so there is a lack of comparative data representing different cultivars. Here, we report, to our knowledge, the first genome-wide transcriptional analysis of 120 RNA samples corresponding to 10 Italian grapevine v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
187
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(203 citation statements)
references
References 96 publications
(135 reference statements)
16
187
0
Order By: Relevance
“…Within each sampling stage, we scheduled the day of sampling in a genotype‐specific manner, in order to collect berries synchronized by phenology across genotypes. Shifts in phenology among genotypes widened as berry development progressed (Massonnet et al ., ). At P and PV stages, the interval of sampling spanned 3 and 4 days, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Within each sampling stage, we scheduled the day of sampling in a genotype‐specific manner, in order to collect berries synchronized by phenology across genotypes. Shifts in phenology among genotypes widened as berry development progressed (Massonnet et al ., ). At P and PV stages, the interval of sampling spanned 3 and 4 days, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental conditions for gene expression analyses are described in Massonnet et al . (). RNA‐seq raw reads are stored in NCBI Gene Expression Omnibus (GEO) under accession numbers and .…”
Section: Methodsmentioning
confidence: 97%
“…3). Content in anthocyanins has been 2 0 described as a reliable indicator of the ripening stage [42]. Additionally, recent 2 1 metabolomics data did not show significant differences in the main ripening parameters 2 2 between control berries of the two cultivars (data not shown).…”
Section: Phenotypic Characterization Of Infected and Mock-treated Gramentioning
confidence: 93%
“…Grape berries undergo a series of complex physiological and biochemical changes during their development that determine their characteristics at harvest (Kuhn et al 2014). Genome-wide expression studies using microarray and, more recently, RNA sequencing (RNA-seq) revealed that berry development involves the expression and modulation of approximately 23,000 genes (Massonnet et al 2017a) and that the ripening transition is associated with a major transcriptome shift (Fasoli et al 2012). Transcriptomic studies characterized the ripening program across grapevine cultivars (Venturini et al 2013;Da Silva et al 2013;Jiao et al 2015;Massonnet et al 2017a),…”
Section: Introductionmentioning
confidence: 99%
“…identifying key ripening related genes (Palumbo et al 2014;Massonnet et al 2017a) and determining the impact of stress and viticultural practices on ripening (Deluc et al 2009;Pastore et al 2013;Xi et al 2014;Blanco-Ulate et al 2015Corso et al 2015;Hopper et al 2016;Savoi et al 2016;Zenoni et al for any grape cultivar. Although the V. vinifera genome is relatively small (~487Mb) (Lodhi and Reisch 1995;Jaillon et al 2007) and as repetitive as other plant genomes of similar size (41.4%) (Jaillon et al 2007;Michael and Jackson 2013), it is highly heterozygous (~13%) (Jaillon et al 2007;Velasco et al 2007).…”
Section: Introductionmentioning
confidence: 99%